Controlling the Composition and Position of Metal–Organic Frameworks via Reactive Inkjet Printing. Issue 12 (22nd March 2023) - Gregory, David Alexander; Nicks, Joshua; Artigas‐Arnaudas, Joaquin; Harris, Michael S.; Foster, Jonathan A.; Smith, Patrick J.
Abstract: Reactive inkjet printing (RIJ) is demonstrated as a new approach to the patterning of surfaces with metal–organic frameworks (MOFs). RIJ is an emerging manufacturing technique that jets solutions of reagents onto a substrate allowing them to react in situ to form the desired material. MOFs have the potential to perform a variety of useful sensing, catalytic, separation and storage applications within sophisticated devices, however, their insolubility makes them challenging to process into complex shapes and patterns. The RIJ approach offers advantages over conventional inkjet printing in that it allows stable solutions of different ligand and metal ions to be combined in a "mix‐and‐match" way. Here, the benefits of the RIJ approach are demonstrated to optimize the stoichiometry of the printed MOF, print a variety of different frameworks using common inks, and create gradients where the composition of the printed MOFs gradually varies between one isoreticular structure and another. Proof of principle is also demonstrated for the approach by demonstrating size selective encapsulation of a dye within a RIJ printed MOF. It is anticipated that this approach will be broadly applicable to the printing of MOFs and related materials enhancing their use across a variety of different applications. Abstract : Reactive inkjet printing (RIJ) is demonstrated as a new approach to the patterning of surfaces with metal‐organic frameworks (MOFs). Here, the benefits of the RIJ approach to print a variety different MOFs, optimize their stoichiometry, and create gradients where the composition of the printed MOFs gradually varies between one isoreticular structure and another are shown.